Females roles and their social world in al-Andalus - Riza Afita Surya,; Daya Negri Wijaya, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This work discusses the social world of Muslim women in medieval Spain. The 8th-12th centuries Islamic society in Spain and its conflict of interest could be fully understood if it is studied in different layers. Previous scholars have already exploited Muslim women studies, but they rarely revisit the medieval Muslim women. This work, therefore, sticks on women world during the period of Al-Andalus (the Islamic Spain). Muslim women in Al-Andalus were commonly portrayed as oppressed and marginalized based on the Western perspective. However, many legal sources indicate the intention of limiting women, but other shows different point of view. Women in Al-Andalus actively participated in many aspects of life, such as political, literate, social, arts, religious and intellectual, and military affairs. Compared to other Muslim women in the Middle East, they had a freedom to conduct what they wanted to do. Its peculiarity had been created due to the Islamic-Christian assimilation in the Islamic Spain.